Elevated Atmospheric CO2 and Nitrogen Fertilization Affect the Abundance and Community Structure of Rice Root-Associated Nitrogen-Fixing Bacteria - Liu, Jumei; Han, Jingjing; Zhu, Chunwu; Cao, Weiwei; Luo, Ying; Zhang, Meng; Zhang, Shaohua; Jia, Zhongjun; Yu, Ruihong; Zhao, Ji; Bao, Zhihua (Frontiers in microbiology, 2021)
Elevated atmospheric CO 2 (eCO 2 ) results in plant growth and N limitation, yet how root-associated nitrogen-fixing bacterial communities respond to increasing atmospheric CO 2 and nitrogen fertilization (eN) during the growth stages of rice is unclear. Using the nifH gene as a molecular marker, we studied the combined effect of eCO 2 and eN on the diazotrophic community and abundance at two growth stages in rice (tillering, TI and heading, HI). Quantitative polymerase chain reaction (qPCR) showed that eN had no obvious effect on nifH abundance in rice roots under either ambient CO 2 (aCO 2 ) or eCO 2 treatment at the TI stage; in contrast, at the HI, nifH copy numbers were increased under eCO 2 and decreased under aCO 2 . For rhizosphere soils, eN significantly reduced the abundance of nifH under both aCO 2 and eCO 2 treatment at the HI stage. Elevated CO 2 significantly increased the nifH abundance in rice roots and rhizosphere soils with nitrogen fertilization, but had no obvious effect without N addition at the HI stage. There was a significant interaction [CO 2 × N fertilization] effect on nifH abundance in root zone at the HI stage. In addition, the nifH copy numbers in rice roots were significantly higher at the HI stage than at the TI stage. Sequencing analysis indicated that the root-associated diazotrophic community structure tended to cluster according to the nitrogen fertilization treatment and that Rhizobiales were the dominant diazotrophs in all root samples at the HI stage. Additionally, nitrogen fertilization significantly increased the relative abundance of Methylosinus ( Methylocystaceae ) under eCO 2 treatment, but significantly decreased the relative abundance of Rhizobium ( Rhizobiaceae ) under aCO 2 treatment. Overall, the combined effect of eN and eCO 2 stimulates root-associated diazotrophic methane-oxidizing bacteria while inhibits heterotrophic diazotrophs.